CFD Analysis of Interference Factor in Hydrofoil-Supported Catamarans (HYSUCAT) - Firdhaus, Ahmad; Kiryanto, Kiryanto; Rindo, Good; Trimulyono, Andi (Department of Naval Architecture - Diponegoro University, 2024)
Catamaran, with its distinctive dual-hull design, offers unique advantages in maritime applications, including improved stability and space utilization over traditional monohull vessels. However, the interaction between the two hulls generates complex hydrodynamic phenomena, significantly influencing the vessel's overall performance. One critical aspect of this interaction is the interference factor, which affects the hydrodynamic resistance encountered by the vessel. The purpose of this paper is to investigate the changes in hydrodynamic characteristics that occur when hydrofoils are incorporated into typical catamaran hull forms. This is accomplished through the utilization of advanced Computing Fluid Dynamics (CFD) simulations. In this study, a Delft-372 catamaran with a concept design is modified by installing a foil system with a high Reynolds number in order to reduce its overall resistance. The new system is then analyzed in order to determine the impact that it has on interference factors. For the purpose of achieving a comprehensive understanding of hydrodynamic behavior, the simulations are carried out under a variety of operating conditions, which include a variety of speeds. Simulations result indicate that the interference factor consistently increases drag for hydrofoil-supported catamarans to more than double that of monohulls across all speeds, particularly when hydrofoil-induced flow disturbances adversely affect the hull's boundary layer, leading to reduced efficiency.